Strategic thinking for smaller businesses and divisions - Lasher, William (Malden, MA : Blackwell Business, 1999)
This book is about: Strategies ideas; Creating a strategic framework; Strategic planning and implementation; Strategic issues for small businesses; Restructuring strategies; ...
Keywords: Business; Management; Strategic planning; Small business; Strategic planning; Small business -- Planning